Hemocompatibility of gallium-68 labeled iron oxide nanoparticles coated with 2,3-dicarboxypropane-1,1-diphosphonic acid - Karageorgou, MA; Bouziotis, P.; Vranjes-Djuric, S; Stamopoulos, D. (MATERIALS SCIENCE & ENGINEERING C-MATERIALS FOR BIOLOGICAL APPLICATIONS, 2020)
Dual-modality contrast agents (DMCA), such as radiolabeled magnetic nanoparticles, have attracted significant attention in diagnostic applications due to their potency for the timely and accurate diagnosis of diseases. The hemocompatibility of a candidate DMCA with human blood is essential for the investigation of its application in vivo. In this respect, here we focused on the evaluation of the hemocompatibility of a new DMCA, that is based on iron oxide nanoparticles (i.e. Fe3O4 magnetite), with human red blood cells (RBCs). The specific iron oxide nanoparticles are surface functionalized with 2,3-dicarboxypropane-1,1-diphosphonic acid (-DPD) and radiolabeled with gallium-68 (Ga-68), resulting in Ga-68-DPD-Fe3O4. RBCs of five healthy individuals are incubated at room temperature for 120 min without and with Ga-68-DPD-Fe3O4 at concentrations 0.1 and 1.0 mg/ml. Optical microscopy (OM) and atomic force microscopy (AFM) are employed to assess detailed information on the overall morphological and geometrical characteristics of the entire cell at the microscopic (10(-6) m) level and on the membrane morphology at the nanoscopic (10(-9) m) level. In addition, a standard hematology analyzer (HA) is used to obtain complete blood count information. At the microscopic level, the combined OM, AFM and HA data revealed that the overall shape/size characteristics of RBCs were preserved upon incubation with Ga-68-DPD-Fe3O4 . However, at the nanoscopic level, the AFM results revealed two different kinds of local deconstructions of the RBCs membrane, termed holes and ulcerlike abnormalities, that were observed in both the DMCA-free and DMCA-incubated samples. Holes did not exhibit any statistically significant difference upon incubation with the Ga-68-DPD-Fe3O4 DMCA. On the contrary, ulcer-like abnormalities exhibited two statistically significant differences upon incubation with the Ga-68-DPD-Fe3O4 DMCA. First, increased percentage of RBCs having at least one ulcer-like abnormality; in DMCA-incubated samples 78.6 +/- 11.6% for C-DMCA = 0.1 mg/ml and 80.4 +/- 11.1% for C-DMCA = 1.0 mg/ml, while in DMCA-free samples 61.2 +/- 8.4% prior to and 63.6 +/- 13.5% after incubation. Second, increased number of ulcer-like abnormalities per RBC; in DMCA-incubated samples 4.26 +/- 0.62 for C-DMCA = 0.1 mg/ml and 3.99 +/- 0.97 for C-DMCA = 1.0 mg/ml, while in DMCA-free samples 2.84 +/- 0.54 prior to and 2.98 +/- 0.50 after incubation. The combined OM, AFM and HA results prove fair hemocompatibility of the Ga-68-DPD-Fe3O4 DMCA with human RBCs, thus documenting its potential use in imaging applications.